Analisis Pengaruh Kualitas Pelayanan Dan HargaTerhadap Kepuasan Pelanggan( Studi kasus pada bengkel service Honda CAHAYA SAKTI MOTORJl. Dr. Rajiman No.657, Surakarta ) - Setya Buana, Arya Anggatra; , Basworo Dibyo, S.E., M.Si (2017)
The purpose of this study is to analyze the quality of service and price to customer satisfaction partially Honda workshop or together. This type of research is a quantitative research, with the consumer population Honda workshop of 100 people consumer, with a sample of 100 consumers. Sampling Sampling technique using saturated or total sampling. Methods of collecting the data research using questionnaires with liket scale. Data analysis of the data analysis technique used test instrument, classical assumption test, multiple linear regression. Based on the results of calculations from the T test, F test, shows the quality of service and price variables together have a significant influence on customer satisfaction. Coefficient of Determination R² 0.577 Obtained result meaning variables of service quality and price Able to explain to variation of change of the variable of customer satisfaction equal to 57.7%, the rest can be explained other variables not found in research models.